2017
DOI: 10.3390/molecules22111898
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Non-Cytotoxic Peptide (p-BthTX-I)2 and Its Serum Degradation Product against Multidrug-Resistant Bacteria

Abstract: Antimicrobial peptides can be used systemically, however, their susceptibility to proteases is a major obstacle in peptide-based therapeutic development. In the present study, the serum stability of p-BthTX-I (KKYRYHLKPFCKK) and (p-BthTX-I)2, a p-BthTX-I disulfide-linked dimer, were analyzed by mass spectrometry and analytical high-performance liquid chromatography (HPLC). Antimicrobial activities were assessed by determining their minimum inhibitory concentrations (MIC) using cation-adjusted Mueller–Hinton br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…This led to a more potent antibacterial action, but also increased the hemolytic effect (Yu et al, 2010). ably, the peptide showed no effect against C. albicans, epithelial cells, erythrocytes and macrophages, demonstrating in this way that it is selective against prokaryotic cells (Santos-Filho et al, 2015).…”
Section: S V Pla 2 S-inspired Antimicrobial Peptidesmentioning
confidence: 87%
See 4 more Smart Citations
“…This led to a more potent antibacterial action, but also increased the hemolytic effect (Yu et al, 2010). ably, the peptide showed no effect against C. albicans, epithelial cells, erythrocytes and macrophages, demonstrating in this way that it is selective against prokaryotic cells (Santos-Filho et al, 2015).…”
Section: S V Pla 2 S-inspired Antimicrobial Peptidesmentioning
confidence: 87%
“…According to the authors, p-BthTX-I exerts a mechanism of action different from the peptide-membrane interaction models most frequently associated to α-helical AMPs (Santos-Filho et al, 2015). This was supported by CF assays also performed, as measurement of fluorescence emission upon calcein release demonstrated that p-BthTX-I had a low interaction with membrane models (POPC and POPC:POPG).…”
Section: S V Pla 2 S-inspired Antimicrobial Peptidesmentioning
confidence: 93%
See 3 more Smart Citations